2023
DOI: 10.1108/srj-03-2022-0153
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and employee engagement: the mediating role of personal environmental norms and employee green behavior

Abstract: Purpose This paper aims to investigate the influence of corporate social responsibility (CSR) on employee engagement (EE) through mediating effect of personal environmental norms (PEN) and employee green behavior (EGB). Design/methodology/approach The proposed model was validated using 360 employees data from manufacturing and service industries. Findings The findings confirmed that CSR is the positive and significant driver of EE. The results also demonstrated PEN and green employee behavior partly mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 109 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Employees with high self-esteem are more likely to be engaged in their work because they feel valued, competent, and capable of making significant contributions to the organization, which become manifold under higher EWE. Ansari and Irfan (2023) and Ansari et al (2021) also found positive contextual effects of EWE in fostering EGBs through enabling the mediating psychological mechanisms like FSE.…”
Section: The Moderating Role Of Ewe In the Fse-egb Linkmentioning
confidence: 87%
See 1 more Smart Citation
“…Employees with high self-esteem are more likely to be engaged in their work because they feel valued, competent, and capable of making significant contributions to the organization, which become manifold under higher EWE. Ansari and Irfan (2023) and Ansari et al (2021) also found positive contextual effects of EWE in fostering EGBs through enabling the mediating psychological mechanisms like FSE.…”
Section: The Moderating Role Of Ewe In the Fse-egb Linkmentioning
confidence: 87%
“…Finally, hypothesis 4(b), which assumed a positive moderation effect of EWE on the FSE-EGB linkage, also found adequate empirical support, which is in line with some of the previous studies. According to Ansari and Irfan (2023), the relationship between FSE and their behavior in times of crisis is significantly influenced by employee engagement. In times of crisis, employees are required to demonstrate adaptability, resilience, and sound decision-making in the face of unprecedented obstacles.…”
Section: Discussionmentioning
confidence: 99%